Effect of Hot Forging Pressure and Heat Treatment on CW625N Lead Free Brass Alloy Dezincification Resistance - (:unkn) unknown (POLISH ACAD SCIENCES INST PHYSICS, 2020)
Brass alloys, like most materials, suffer from the inevitable effect of corrosion. The CW625N (CuZn35Pb1) alloy is called a lead-free alloy because it contains a maximum of 1.6% Pb in its composition. It is suitable for hot forging, and is a new type of alloy. In this study, CW625N brass alloy test samples were shaped by hot forging. Heat treatment of some of the formed test samples and the effect of these processes on hardness, microstructure, and dezincification resistance were investigated. Forging temperature was kept constant at 750 degrees C and forging pressure was 70 bar and 90 bar. The samples from the hot forging were cooled in calm air. A portion of the test samples cooled in calm air were heat treated at 550 degrees C for 2.5 h. The heat treated test samples were compared with the non-heat treated test samples. When the hardness values of the heat treated samples were examined, it was seen that they were harder than the non-heat treated samples. Metallographic examination showed that the grain sizes of the heat treated samples decreased and the dezincification resistance was high. When the microstructures were examined, it was seen that needle-shaped structures were formed in the samples which were forged under 90 bar and heat treated. Increase of forging pressure enhanced the hardness and the grain size. However, there were no direct effect on dezincification resistance.